2008
DOI: 10.1002/pd.2067
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance of preimplantation genetic diagnosis for β‐thalassemia in Lebanese women with previously affected children

Abstract: PGD is an acceptable alternative to conventional prenatal diagnosis in women at risk of conceiving a child affected with beta-thalassemia. This is particularly true in countries of the Middle-East where therapeutic abortions for fetal indications are prohibited by the law and religion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 17 publications
1
17
0
1
Order By: Relevance
“…There were studies which had investigated women's attitudes to PGD, including Pergament (1991) who found that the technology was more acceptable to women who had previous abnormal PND results and that the agreed major advantage of PGD was the avoidance of TOP. Participants in other studies included women at risk of transmitting thalassaemia (Palomba et al, 1994;Chamayou et al, 1998;Farra et al, 2008;Hui et al, 2002). These women generally found PGD preferable to PND with higher rates of approval from women who had experienced TOPs or who had an affected child.…”
Section: Context Of Other Studiesmentioning
confidence: 96%
“…There were studies which had investigated women's attitudes to PGD, including Pergament (1991) who found that the technology was more acceptable to women who had previous abnormal PND results and that the agreed major advantage of PGD was the avoidance of TOP. Participants in other studies included women at risk of transmitting thalassaemia (Palomba et al, 1994;Chamayou et al, 1998;Farra et al, 2008;Hui et al, 2002). These women generally found PGD preferable to PND with higher rates of approval from women who had experienced TOPs or who had an affected child.…”
Section: Context Of Other Studiesmentioning
confidence: 96%
“…In the few studies that have examined aspects of decision making surrounding PGD use, investigators worldwide have primarily targeted female partners (Farra et al, 2008; Hui et al, 2002; Karatas et al, 2010a; Miedzybrodzka et al, 1993; Pergament, 1991; Quinn et al, 2009) or have used hypothetical or prospective scenarios (Chamayou et al, 1998; Hui et al, 2002; Kalfoglou et al, 2005; Krones et al, 2005). Other scholars have provided recommendations or opinions as to how genetically at-risk couples should act toward PGD (Cameron & Williamson, 2003; de Wert, 2005; El-Toukhy et al, 2008; Offit et al, 2006; Watt, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Sixty-eight per cent of women considered PGD a better alternative to PND. The most important perceived advantage of PGD was the avoidance of termination of an affected pregnancy (Farra et al 2008) …”
Section: Prenatal Genetic Diagnosis For Haemoglobinopathies In Arab Cmentioning
confidence: 99%